Effects of dietary electrolyte balance on sow and litter performance, blood chemistry, and urine chemistry in lactating sows - Robert H Hines; C A Maloney; D J Lee; D W Dean; H Cao; J S Park; Joel M DeRouchey; Joe D Hancock (Kansas Agricultural Experiment Station Research Reports, 2000)
Decreasing the dietary electrolyte balance (dEB) in diets for lactating sows from 500 to 100 mEq/kg increased piglet survivability but had no effect on litter weight gain. Decreased dEB reduced pH and bacteria in the sows urine and, thus, could influence the health status of the reproductive tract.; Swine Day, Manhattan, KS, November 16, 2000
Keywords: Swine day; 2000; Kansas Agricultural Experiment Station contribution; no. 01-138-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 858; Swine; Sows; Dietary electrolyte balance; Acid-base balance